Predator guards on nest boxes improve nesting success of birds - Robyn L. Bailey; David N. Bonter (Wildlife Society Bulletin)
ABSTRACT Humans have long provided nest boxes in a widespread and popular effort to augment nesting sites for cavity‐nesting birds. Nest boxes, however, may provide easy access for predators and thereby create ecological traps for nesting birds. Predator exclusion techniques are often deployed at nest boxes to reduce nest predation, but few studies have tested their performance. For the first time, we test the effectiveness of predator guards in promoting the nesting success of multiple species of birds at a large spatial scale (United States and Canada). We used nest fate data from 24,114 nest records submitted from 2014 to 2016 to NestWatch, a citizen‐science program focused on quantifying nesting success, to determine whether installing predator guards on nest boxes is an effective management technique. Across all species, top models predicting daily nest survival rates suggest a positive influence of predator guards, with a nearly 7% increase in nest success for attempts in boxes with guards versus attempts in boxes without guards. At the species level, nest survival was greater for individuals nesting in boxes with guards in 7 of 9 species, with no effect in the remaining 2 species. Although all types of guards were correlated with improved nesting success, birds nesting in boxes with cone‐type baffles, stovepipe baffles, or entrance hole extenders were most likely to result in successful nesting. Further, birds nesting in boxes with multiple predator guards were more successful, on average, than birds nesting in boxes with only a single guard. Our results can help managers of cavity‐nesting birds incorporate science‐based evidence into decision‐making and allocate resources more effectively. © 2017 The Wildlife Society.